Vulnerability-deprivation-resilience: A sociotechnical approach to humanitarian logistics management - Luis Yáñez-Sandivari; Felipe Cornejo; Cristián Cáceres (Transportation Research Interdisciplinary Perspectives)
This study develops a sociotechnical framework to explore the interrelations between social vulnerability, deprivation cost, and community resilience in the context of humanitarian logistics. Drawing on survey data from 644 residents in disaster-prone regions in Valparaíso, Chile, we applied confirmatory factor analysis and structural equation modelling to validate latent constructs and assess their interdependencies. Results reveal that higher social vulnerability correlates with increased deprivation cost, whereas resilience exhibits a negative relationship. A bidirectional association between vulnerability and resilience suggests the existence of a dynamic feedback mechanism relevant to post-disaster recovery. Multigroup analyses confirmed the consistency of these associations across subpopulations with varying risk perceptions. The results underscore the operational value of integrating psychosocial variables into preparedness and response strategies to improve anticipatory logistics, resource allocation, and equity in humanitarian contexts. Future research should adopt longitudinal and mixed-methods approaches to embed psychosocial indicators within real-time decision-support systems.